Inheritance of resistance to fusarium wilt (Fusarium oxysporwn f sp ciceri) in gram (Cicer arietinum) - DIKSHIT, H K; SINGH, I S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during winter seasons of 1987-90 to study the inheritance of resistance to will caused by Fusarium oxyporum Schlecht. f Â·sp ciceri (padw.) Matuo & Salo, using 3 varieties of gram (Cieer arietinum L.). 'JG 74' and 'PG 114' were found resistant on screening in pot as well as field. These were crossed with highly susceplible vuriety 'JG 62'. Cross 'JG 74' x 'JG 62' showed monogenic recessive inheritance of resistance. However, 'PG 114' x 'JG 62' showed resistance to wilt under influence of 2 recessive genes. oligogenic nuture of inheritance of resistance to wilt emphasizes the need of bulk population breeding and backcross breeding for development of resistant varieties.